KEWENANGAN KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) DAN KEJAKSAAN AGUNG DALAM EKSEKUSI SANKSI DENDA PADA KASUS PERSAINGAN USAHA DI INDONESIA - Aisyah Syifaa Suwita (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2023)
This study examines two formulations of the problem, namely what is the authority of the Business Competition Supervisory Commission (KPPU) in executing fines in business competition cases in Indonesia and what is the authority of the Attorney General's Office in executing fines in business competition cases in Indonesia. The research methodology used by the author is a normative research method with a statutory review approach. The conclusion obtained is that KPPU does not have the authority to execute fines on KPPU decisions but must go through the District Court. However, after the Job Creation Law, the authority regarding objections to the KPPU's decision was submitted to the Commercial Court. Then related to the authority of the Prosecutor's Office in executing fines in KPPU's decisions is based on a Memorandum of Understanding between KPPU and the Attorney General's Office and followed up with a Special Power of Attorney from KPPU to the Deputy Attorney General for Civil and State Administration regarding the settlement of fines in KPPU decisions.